2010
DOI: 10.1519/jsc.0b013e3181f0a76a
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Anthropometric and Physiological variables and Bat Velocity of High-School Baseball Players Before and After 12 Weeks of Training

Abstract: The purpose of this article was to investigate the relation between anthropometric and physiological variables to linear bat swing velocity (BV) of 2 groups of high-school baseball players before and after completing a 12-week periodized resistance exercise program. Participants were randomly assigned to 1 of 2 training groups using a stratified sampling technique. Group 1 (n = 24) and group 2 (n = 25) both performed a stepwise periodized resistance exercise program and took 100 swings a day, 3 d·wk-1, for 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 10 publications
2
42
0
Order By: Relevance
“…This device provided instant feedback concerning BV (16) and has been used in previous research (7,(19)(20)(21). The chronograph is no larger than a small alarm clock.…”
Section: Instrumentationmentioning
confidence: 99%
“…This device provided instant feedback concerning BV (16) and has been used in previous research (7,(19)(20)(21). The chronograph is no larger than a small alarm clock.…”
Section: Instrumentationmentioning
confidence: 99%
“…On the one hand, the lower body mass in relation to active mass is conductive to train for speed and endurance, which is typical in short track (Hoffman et al 2009;Nemoto et al 1990). On the other hand, during such a training, the economy of energy reserve usage is being increased which constitute a competitor's protection from a sudden decrease of physical effort ability (Buglione et al 2011;Costa et al 2012;Szymański et al 2010). According to Bomp and Haff (2010) the basic factor determining high effort adaptation during endurance sports like short track, is not training volume, but adequate diversity of trainings and various intensity ranges.…”
Section: Discussionmentioning
confidence: 99%
“…Core training is rarely performed as an isolated training modality, but rather as part of a larger overall fitness routine. Therefore, it is not surprising that seven studies [911,18,20,26,27] reported significant improvements in maximum lift performance during post-testing. Likewise, it seems intuitive that interventions that targeted the core would show improvements in measures of core stability and endurance.…”
Section: Discussionmentioning
confidence: 99%